(untitled) (Perspectivas em Ciência da Informação, 2011)
This paper evaluates the level of success of users of the CAPES Digital Library of Scientific Journals, when searching for a specific journal and the reasons for their failures. The methodology used was quantitative with some qualitative data collected. The study used descriptive statistics to analyze two questions of a survey concerning the Portal´s user satisfaction which were answered by 930 faculty members of 17 universities in Brazil. The areas of knowledge investigated were Biological Sciences, Humanities and Linguistics, Literature and the Arts. The results show that 645 (70%) of the researchers are almost always or frequently successful when searching for a specific journal in the Portal. Researchers in Linguistics, Literature and the Arts are the least successful. For 76% of the researchers, the main reason for not obtaining success is the absence of the journal in the collection. Responses to open questions reveal that, especially for older literature, the journal might be present in the collection but the specific issue needed may be absent or access to full text of the particular article sought may be restricted. Reasons for failure related to factors such as usability, difficulty with foreign languages and lack of training or difficulties for access were less cited by respondents.